Molecular evidence for stimulation of methane oxidation in Amazonian floodplains by ammonia-oxidizing communities - Monteiro, Gabriel G. T. N.; Barros, Dayane J.; Gabriel, Gabriele V. M.; Venturini, Andressa M.; Veloso, Tomás G. R.; Vazquez, Gisele H.; Oliveira, Luciana C.; Neu, Vania; Bodelier, Paul L. E.; Mansano, Cleber Fernando M.; Tsai, Siu M.; Navarrete, Acacio A. (Frontiers in Microbiology, 2022)
Ammonia oxidation is the rate-limiting first step of nitrification and a key process in the nitrogen cycle that results in the formation of nitrite (NO2–), which can be further oxidized to nitrate (NO3–). In the Amazonian floodplains, soils are subjected to extended seasons of flooding during the rainy season, in which they can become anoxic and produce a significant amount of methane (CH4). Various microorganisms in this anoxic environment can couple the reduction of different ions, such as NO2– and NO3– with the oxidation of CH4 for energy production, and effectively link the carbon and nitrogen cycle. Here, we addressed the composition of ammonium (NH4+) and NO3 – - and NO2– - dependent CH4-oxidizing microbial communities in an Amazonian floodplain. In addition, we analyzed the influence of environmental and geochemical factors on these microbial communities. Soil samples were collected from different layers of forest and agroforest land-use systems during the flood and non-flood seasons in the floodplain of the Tocantins River, and next-generation sequencing of archaeal and bacterial 16S rRNA amplicons was used, coupled with chemical characterization of the soils. We found that ammonia-oxidizing archaea (AOA) were more abundant than ammonia-oxidizing bacteria (AOB) during both flood and non-flood seasons. Nitrogen-dependent anaerobic methane oxidizers (N-DAMO) from both the archaeal and bacterial domains were also found in both seasons, with higher abundance in the flood season. The different seasons, land uses, and depths analyzed had a significant influence on the soil chemical factors and also affected the abundance and composition of AOA, AOB, and N-DAMO. During the flood season, there was a significant correlation between ammonia oxidizers and N-DAMO, indicating the possible role of these oxidizers in providing oxidized nitrogen species for methanotrophy under anaerobic conditions, which is essential for nitrogen removal in these soils.